2023
DOI: 10.1001/jamanetworkopen.2023.0999
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries in Medicaid-Insured Preschool Children With or Without Special Health Care Needs in Northeast Ohio

Abstract: ImportanceChildren with special health care needs (CSHCN) are recognized to be at increased risk of developing dental caries (decay). Evidence is mixed regarding the association of preventive oral health care delivered by pediatric primary care clinicians with caries experience among CSHCN.ObjectiveTo investigate caries experience, including untreated decay, among Medicaid-enrolled preschoolers with or without special health care needs.Design, Setting, and ParticipantsThis cross-sectional study used baseline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Moreover, the current study found that the dmft values of children in the SD group were significantly lower than that of healthy patients. This is in line with the findings of Ronis et al [35], who noted better oral health in special needs preschoolers than healthy children. Hence a presumption of poorer oral health and challenges in children with SD may be unfounded.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the current study found that the dmft values of children in the SD group were significantly lower than that of healthy patients. This is in line with the findings of Ronis et al [35], who noted better oral health in special needs preschoolers than healthy children. Hence a presumption of poorer oral health and challenges in children with SD may be unfounded.…”
Section: Discussionsupporting
confidence: 93%
“…Nationally, 17.8% of 2- to 8-year old children in the US living below the federal poverty level have untreated dental caries (ie, tooth decay and cavities) . Previous analyses of 3- to 6-year-old Medicaid-insured children from the cohort analyzed in this current study have shown an even higher prevalence of 29% . Receipt of preventive dental services among Medicaid-enrolled children nationally has risen from 42% to 48% between 2011 to 2018, but the national goal of 52% remains unmet…”
Section: Introductionmentioning
confidence: 53%
“…1 Previous analyses of 3-to 6-year-old Medicaidinsured children from the cohort analyzed in this current study have shown an even higher prevalence of 29%. 2 Receipt of preventive dental services among Medicaid-enrolled children nationally has risen from 42% to 48% between 2011 to 2018, but the national goal of 52% remains unmet. 3 The disparate burden of dental caries among young children 4 has prompted recommendations for primary care clinicians to provide preventive oral care for children 5 years and younger, including referral to a dentist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation